Competitive Endogenous Role of the LINC00511/miR-185-3p Axis and miR-301a-3p From Liquid Biopsy as Molecular Markers for Breast Cancer Diagnosis - Mahmoud, Marwa M.; Sanad, Eman F.; Elshimy, Reham A.A.; Hamdy, Nadia M. (Frontiers in Oncology, 2021)
Breast cancer (BC) is the leading cause of female cancer-related mortalities. Evidence has illustrated the role of long non-coding RNAs (lncRNA) and microRNAs (miRNA) as promising pool of protein non-coding regulators, for tuning the aggressiveness of several malignancies. This research aims to unravel the expression pattern and the emphases of the diagnostic value of the long intergenic ncRNA00511 (LINC00511) and its downstream microRNA (miR-185-3p) and the pathogenic significance of the onco-miR-301a-3p in naïve BC patients. LINC00511 was chosen, validated and its molecular binding was confirmed using bioinformatics. LINC00511 was measured in 25 controls and 70 patients using qPCR. The association between the investigated ncRNA’s expression and the BC patients’ clinicopathological features were assessed. Receiver operating characteristic (ROC) curve was blotted to weigh out their diagnostic efficacy over the classical tumor markers (TMs). Bioinformatics and spearman correlation were used to predict the interaction between LINC00511, miR-185-3p and miR-301a-3p all-together to patients’ features. LINC00511 and miR-301a-3p, in BC patients’ blood, were overexpressed, their median levels increased, significantly, while, miR-185-3p was contrarily down-regulated, being decreased 4-folds. LINC00511 was elevated in BC early-stages, when compared to late-stage (P<0.0003). LINC00511, miR-185-3p and miR-301a-3p showed AUC superior to classical TMs, letting us to conclude that the investigated ncRNA’s, in BC patients’ liquid biopsy, are novel diagnostic molecular biomarkers signature. Lymph-node metastasis (LNM) and advanced tumor grade were directly correlated with LINC00511, significantly. Additionally, both LINC00511, miR-301a-3p were positively correlated with the aggressiveness of BC, as manifested in patients with larger tumors (>2 Cm) at (P<0.001). Therefore, these findings aid our understanding of BC pathogenesis, in the clinical setting, being related, in part to, LINC00511/miR axis, that could be a future potential therapeutic target.